2012
DOI: 10.1080/08870446.2011.609595
|View full text |Cite
|
Sign up to set email alerts
|

Examining predictors of physical activity among inactive middle-aged women: An application of the health action process approach

Abstract: This study tested several relationships predicted by the Health Action Process Approach (HAPA) in a sample of 175 generally healthy, inactive, middle-aged women (40–65 yrs old) over a 12 week period. Participants’ physical activity, risk perceptions, outcome expectancies, action self-efficacy, and intentions were measured at baseline. Planning and maintenance self-efficacy were measured four weeks later. Physical activity behaviour was measured twelve weeks after baseline. The HAPA relationships were examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
76
8
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(105 citation statements)
references
References 56 publications
19
76
8
2
Order By: Relevance
“…The significant strong correlation between action self-efficacy and behavioural intention in the motivational stage is in line with correlational findings of previous research (Bandura, 1982;Bassett, 2006;Lippke, Ziegelmann, and Schwarzer, 2004;Schwarzer et al, 2007), and supportive of the predictive ability that action self-efficacy has been found to have with behavioural intentions (Barg et al, 2012;Luszczynska and Schwarzer, 2003;Scholz, Sniehotta, and Schwarzer, 2005). These findings point to people who feel efficacious about undertaking their exercises being likely to follow through with their intentions (Sniehotta, Scholz, and Schwarzer, 2005a).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The significant strong correlation between action self-efficacy and behavioural intention in the motivational stage is in line with correlational findings of previous research (Bandura, 1982;Bassett, 2006;Lippke, Ziegelmann, and Schwarzer, 2004;Schwarzer et al, 2007), and supportive of the predictive ability that action self-efficacy has been found to have with behavioural intentions (Barg et al, 2012;Luszczynska and Schwarzer, 2003;Scholz, Sniehotta, and Schwarzer, 2005). These findings point to people who feel efficacious about undertaking their exercises being likely to follow through with their intentions (Sniehotta, Scholz, and Schwarzer, 2005a).…”
Section: Discussionsupporting
confidence: 88%
“…This indication is further demonstrated by the moderate to strong correlations between the self-efficacies and intentions. While not being a new finding, it is consistent with other similar physiotherapy research in which moderate correlations were found between self-efficacy and behavioural intentions (Barg et al, 2012;Bassett and Prapavessis, 2011). The mean scores and correlations between the self-efficacies suggest the presence of an underlying construct and while each measure was able to differentiate the associated beliefs of the specific self-efficacy, the validity of the underlying construct was also being measured.…”
Section: Discussionsupporting
confidence: 81%
“…With respect to severity, we examined several similar (i.e., absolute risk and relative vulnerability) constructs, but none of these were significantly associated with the remaining constructs. It should be noted that other studies have observed similar nonsignificant relationships as ours . It could be that the high prevalence of comorbidities in this population may shield the impact that being at risk for a specific outcome may have on PA. Severity may play an important role in the consequences of PA, rather than the antecedents in this sample.…”
Section: Discussionsupporting
confidence: 76%
“…According to the findings, lack of physical activity is more common in women than in men and in older age groups (Hallal, 2012;Hawkins et al, 2009). It appears that physical activity in middle age, especially in middle-aged women, leads to lifestyle modifications that extend in to older ages and enhances their quality of life (Barg et al, 2012). The study of physical activity in different communities and social groups such as the middle aged populations helps planners and decision makers to identify patterns and factors of influencing these patterns and to initiate effective interventions.…”
Section: Introductionmentioning
confidence: 99%